ANALISIS MANAJEMEN RISIKO USAHA BERDASARKAN TEORI TAWAKAL - Agustin, Hamdi; Setiawan, Rahmat; Zulkifli, Muhammad Ilham; Wan Jumiati (JSE: Jurnal Sharia Economica, 2026)
This study aims to analyze operational risk management based on the theory of tawakal. The risk management analysis based on the theory of tawakal consists of human resource (HR) risks, technological risks, process risks, and environmental risks. This study uses a qualitative approach and was conducted at UD. Cucu Datuok Gemilang Fish Farm in Kampar, Riau. Data collection was carried out through direct observation and interviews. The results of the study indicate that based on the assessment of the foundation aspects of the business owner, UD. Cucu Datuok Gemilang Fish Farm is at low risk, although some of the business capital sources come from usurious loans. The results of the business risk analysis indicate that UD. Cucu Datuok Gemilang Fish Farm faces various risks in the aspects of human resources (HR), technological risks, process risks, and environmental risks. The highest risks that need to be addressed immediately are business capital sources (F3), employee competence and knowledge (A1), employee discipline and work ethic (A2), and the consistency of fish feed availability (C4). In the risk evaluation, strategies are carried out according to the risks that will occur. Such as evaluating risks on employee competence and knowledge, employee discipline and work ethic by conducting employee performance assessments.